Review Langman’s Medical Embryology / 13th edition. – LWW, 2014. – 424 p. - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2015)
Offering exceptional full-color diagrams and clinical images, Langman’s Medical Embryology, the 13th edition (Langman Medical Embryology) helps physicians, nurses and medical students develop a basic understanding of embryology and its clinical implications.